2005
DOI: 10.2105/ajph.2003.023077
|View full text |Cite
|
Sign up to set email alerts
|

School District Resources and Identification of Children With Autistic Disorder

Abstract: District revenue was associated with higher proportions of children identified with autistic disorder at baseline and increasing rates of identification when measured longitudinally. Economically disadvantaged communities may need assistance to identify children with autistic spectrum disorders and other developmental delays that require attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 53 publications
4
58
2
1
Order By: Relevance
“…Children in counties with greater urban density had lower proportions of medication use. Similarly, Palmer et al 22 showed that greater urban density at the county level was associated with more identification of children with ASD. Urban areas, as well as areas with a higher proportion of white residents, may have access to academic health settings where there is greater familiarity with developmental delays.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Children in counties with greater urban density had lower proportions of medication use. Similarly, Palmer et al 22 showed that greater urban density at the county level was associated with more identification of children with ASD. Urban areas, as well as areas with a higher proportion of white residents, may have access to academic health settings where there is greater familiarity with developmental delays.…”
Section: Discussionmentioning
confidence: 95%
“…What is known is that there is considerable county-and state-level variation in the identification of children with ASD, which has been associated with education-related spending, urbanicity, and health care resources. 19,22 Other studies also have found rural/urban 23 and ethnic differences in ASD identification. 24,25 Little is known, however, about how child characteristics and local resources influence medication treatment; therefore, in addition to estimating the prevalence of psychotropic medication use among children with ASDs, we explored the relative contributions of child, county, and state characteristics to its use.…”
mentioning
confidence: 97%
“…Numerous research studies have indicated that ethnicity status does not influence the prevalence of ASD [11][12][13][14][15][16]. Since children from ethnically diverse backgrounds, children have low socioeconomic status, or those with lower educational levels are all underserved populations, we discuss them together as a minority group.…”
Section: Minority Students With Asdmentioning
confidence: 99%
“…Rose et al stated that "learning is supported and facilitated by the interaction between the learner and the curriculum" (p: 19). In fact, if a teacher designs a flexible curriculum to suit individual needs, the chance of academic success is increased [11]. Accordingly, the UDL guidelines offer flexible options that can be integrated into curriculum and instruction to support all diverse students.…”
Section: Implementing Universal Design For Learning (Udl)mentioning
confidence: 99%
“…However, there are significant differences in how states define and assess children for eligibility (Conderman & Katsiyannis, 1996). The administrative prevalence of children in the "Autism" special education category varies across states, across school districts within a state, and appears to be significantly associated with education-related spending as well as availability of health-related resources Palmer, Blanchard, Jean, & Mandell, 2005). Although it appears to be more common for children with Autistic Disorder to be identified during the preschool period, many children are first identified by their local school system, not their local health care system (Yeargin-Allsopp et al, 2003).…”
mentioning
confidence: 99%